The Legal System for Contracting a Bank Loan in Iraqi Law - Amera Jaafar Shareef; Helmet Muhammed Asaad; Kamaran Mohammed Qadir (QALAAI ZANIST JOURNAL, 2023)
Bank loans are an effective element in activating, developing and modernizing the national economy in all respects, especially the aspects related to the infrastructure of the Kurdistan Region - Iraq, and due to the lack of banking awareness and the lack of effective laws to reduce risks related to the operation of banks in general and loans in particular, as well as the loss of confidence in banks by merchants and citizens Because of the lack of cash in most of the region's banks, bank loans did not achieve the desired goals. On the other hand, most of the banks in Iraq are usurious banks, which discourages people from dealing with them, and for all that we have tried in this research to shed light on some aspects of bank loans by clarifying the definition of the bank loan contract in several laws and language dictionaries, and then choosing this definition: (bank loan: It is credit, and it means those services provided by which individuals, institutions and establishments in the community are provided with the necessary funds, provided that the debtor undertakes to pay those funds and their interests on time. A bank loan has certain characteristics, as it is a consensual contract, a binding contract for both sides, and a donation contract in the first place, and it can be a netting contract if interest is stipulated for it. In all fields, and since there are risks to these loans, personal and in-kind guarantees have been put in place, in order to preserve them from loss, and work to eliminate the banking risks that surround them. After the study, several conclusions and recommendations were reached at the conclusion of the research.